Diagnosis and Treatment of Foreign Body in The Respiratory Tract in Children - Isakov Abdurauf Mamadiyarovich (Journal of Science in Medicine and Life, 2024)
A foreign body in the respiratory tract in children is the presence of foreign objects in the larynx or trieobronchial tree of a child. The problem is mainly diagnosed in patients under 5 years of age. Organic (pieces of food, seeds, extracted teeth) and inorganic particles (coins, buttons, parts from toys) can enter the respiratory system. The condition is manifested by a sudden attack of choking and coughing, a blue face, and restlessness of the child. Diagnosis is carried out on an emergency basis according to anamnesis, radiography, and bronchoscopy. Treatment involves removing the foreign body endoscopically or during classical surgery.